Analysis of American Cutaneous Leishmaniasis cases in Brazil (Research, Society and Development, 2024)
American Cutaneous Leishmaniasis (ATL) is a notifiable, infectious, non-contagious disease caused by more than 20 protozoa belonging to the genus Leishmania. Tegumentary Leishmaniasis has a high rate of cases in America, mainly in Brazil. The lesion causes ulcers on the skin and mucous membranes of the upper airways. First, papulonodular, painless lesions appear, which may be eroded or ulcerated, with a granular background. In some cases, the lesions have a purulent background with well-defined, high and erythematous edges. Lesions caused by cutaneous Leishmaniasis are directly associated with unsightly scars that cause low self-esteem and generate emotional impacts on patients' lives. This is a quantitative, retrospective, descriptive and cross-sectional study of cases of American Tegumentary Leishmaniasis (ATL), between the years 2015 and 2020 in Brazil. The present study aims to report the epidemiological profile of cutaneous leishmaniasis in Brazil, and consequently, assist in directing measures to control the disease through efficient strategies.